"That building with the palm trees": Wellington Central Library - Pollock, Kerryn (Architectural History Aotearoa, 2020)
Athfield Architects' postmodern Wellington Central Library (1991) represented the firm's entry into public architecture. Part of the Civic Square development, and Aotearoa New Zealand's largest construction project at the time, it was a propitious turn away from the corporate work that went from boom to bust in the wake of the 1987 share market crash. The library was a critical and popular success, winning three major awards and becoming known as "Wellington's living room." Fast forward to 19 March 2019, and it was closed with a few hours warning due to seismic concerns. Fears for its future prompted a public nomination for the New Zealand Heritage List/Rārangi Kōrero. This paper will explore the building's history, design and heritage values.